Fatigue life studies in carbon dual-phase steels - Hashimoto, T. M.; Pereira, Marcelo dos Santos [UNESP] (Elsevier B.V., 1996)
An investigation has been conducted to examine the morphological influence on fatigue life of low carbon steel with dual phase microstructure. The results showed that dual-phase microstructure, composed by ferrite and martensite had superior symmetrical bending fatigue strength when compared with ferrite-pearlite steel. Through those tests, evidences of different mechanisms were verified (such as ferrite cyclic hardening, slip band formation and beginning of crack nucleation and propagation). Based on the fatigue tests results, various mechanisms stages were discussed associated with different microstructure morphology. Copyright (C) 1996 Published by Elsevier B.V. Limited.
Keywords: dual phase steel; fatigue; microstructure